PENGENALAN PRAKTIKUM KIMIA SEDERHANA UNTUK SISWA SMA NEGERI 45 MALUKU TENGAH - Pada, Semuel Simra; Siahaya, Anto Netty; Souhoka, Fensia Analda; Gaspersz, Nelson (Universitas Pattimura, 2025)
This community service aims to improve the quality of chemistry learning at SMA Negeri 45 Maluku Tengah, which has limited laboratory facilities. The majority of students come from farming and fishing families, offering potential for integrating local natural resources into contextual learning. The main challenge for the school is the scarcity of practical tools and materials, leading to difficulties for students in understanding abstract chemical concepts and reducing their interest in learning. Based on these issues, community service activities were designed to introduce simple laboratory tools and materials and develop students' experimental skills. The methodology included preparing materials and equipment (glassware, common reagents), forming a mentoring team consisting of chemistry lecturers and students, socializing the activities, conducting direct practical sessions in small groups with demonstrations, as well as analyzing results and discussions. The results showed an improvement in students' understanding and interest through active participation in practical sessions on introducing glassware, acid-base titration, hydrogen gas formation, and carbon dioxide gas identification tests. Direct observation and question-and-answer sessions indicated that students were able to understand the function of tools, perform titrations correctly, observe chemical reactions, and identify gases. The evaluation demonstrated the program's effectiveness in enhancing students' understanding and practical skills, bridging the theory-practice gap, and fostering interest in chemistry learning